Shedding light on neurofilament involvement in cognitive decline in obstructive sleep apnea and its possible role as a biomarker - Jaromirska, Julia; Kaczmarski, Piotr; Strzelecki, Dominik; Sochal, Marcin; Białasiewicz, Piotr; Gabryelska, Agata (Frontiers in Psychiatry, 2023)
Obstructive sleep apnea is one of the most common sleep disorders with a high estimated global prevalence and a large number of associated comorbidities in general as well as specific neuropsychiatric complications including cognitive impairment. The complex pathogenesis and effects of the disorder including chronic intermittent hypoxia and sleep fragmentation may lead to enhanced neuronal damage, therefore contributing to neuropsychiatric pathologies. Obstructive sleep apnea has been described as an independent risk factor for several neurodegenerative diseases including Alzheimer’s disease and all-cause dementia. The influence of obstructive sleep apnea on cognitive deficits is still a topic of recent debate and several mechanisms underlying this correlation are taken into consideration including neurodegeneration and depression-related cognitive dysfunction. The differentiation between both pathomechanisms of cognitive impairment in obstructive sleep apnea is a complex clinical issue, requiring the use of multiple and costly diagnostic methods. The studies on neuroprotection biomarkers such as brain-derived neurotrophic factor and neurofilaments are recently gaining ground in the topic of cognition assessment in obstructive sleep apnea patients. Neurofilaments as neuron-specific cytoskeletal proteins could be useful non-invasive indicators of brain condition and neurodegeneration, that already are observed in many neurological diseases leading to cognitive deficits. Additionally, neurofilaments play an important role as a biomarker in other sleep disorders such as insomnia. Thus, this review summarizes the current knowledge on the involvement of neurofilaments in cognitive decline and neurodegeneration in obstructive sleep apnea patients as well as discusses its possible role as a biomarker of these changes.